2020
DOI: 10.1080/13880209.2020.1748661
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput assay for screening natural products that boost NK cell-mediated killing of cancer cells

Abstract: Context: Natural killer (NK) cells can eliminate malignant cells and play a vital role in immunosurveillance. Administration of natural compounds represents a promising approach for antitumor immunotherapy, which may enhance the NK cell activity via multiple mechanisms. Objective: Establishing approaches to evaluate the effect of select natural products on NK cell-mediated cytotoxicity. Materials and methods: We selected a natural product library containing 2880 pure compounds, which was provided by the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Previously, we screened nearly 3000 natural products using a high-throughput assay (Gong et al 2015;Xu et al 2020) and found that Red-A increased NK cell-mediated killing of NSCLCs. We demonstrated Red-A could affect the viabilities of A549 and H1299 tumour cells but did not affect the viabilities of NK cells (Figure 1(A-C)).…”
Section: Red-a Blocked Immuno-resistance Of Nsclcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we screened nearly 3000 natural products using a high-throughput assay (Gong et al 2015;Xu et al 2020) and found that Red-A increased NK cell-mediated killing of NSCLCs. We demonstrated Red-A could affect the viabilities of A549 and H1299 tumour cells but did not affect the viabilities of NK cells (Figure 1(A-C)).…”
Section: Red-a Blocked Immuno-resistance Of Nsclcsmentioning
confidence: 99%
“…In search of a natural substance that overcomes tumour immune resistance to NK cells, we performed a high-throughput assay to screen nearly 3000 Chinese medicine-derived small molecular compounds in our previous study (Gong et al 2015;Xu et al 2020). We found that rediocide-A (Red-A) extracted from the roots of Trigonostemon rediocides Craib (Euphorbiaceae) could potentially block tumour immune resistance to NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we established a new luminescence-based high-throughput screening system [11], which could detect percent lysis of tumor cells and its viability with natural products treatment ( Fig. 1A).…”
Section: Thb Exhibits the Most Potent Cytotoxicity To Nsclc Cells Thrmentioning
confidence: 99%
“…In our previous study, we have established a new type of high-throughput screening system to search for natural products with anti-tumor activities [11]. THB is one of the natural product candidates that we used this luminescence-based screening system to nd out, which sensitive to NSCLC cells.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies of the treatment of EAE by TCM monomers containing flavonoids, phenol, and glycosides, among others ( Ciumărnean et al, 2020 ; Ikram et al, 2020 ; Yang L. et al, 2020 ). Moreover, many researchers have studied the effect of chemical monomers by molecular docking, high-throughput screening, and network pharmacology ( Chen et al, 2020 ; Liu J. et al, 2020 ; Xu et al, 2020a ). Over the past 8 years, glycosides have been the most commonly studied compounds, and have been examined and developed with the intent of using them as a potential treatment for EAE ( Giacoppo et al, 2013 ; Yin et al, 2014 ; Haghmorad et al, 2017 ; Madhu et al, 2019 ; Yang L. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%